Application of a new method to investigate population structure in the harbour porpoise, Phocoena phocoena, with special reference to the North and Baltic Seas - Lockyer, Christina (J. Cetacean Res. Manage., 1999)
Tooth ultrastructure in harbour porpoise is examined as a possible tool for differentiating between animals from different geographical regions in the North Atlantic. Nine different characteristics in both dentine and cementum are identified and recorded in the decalcified, sectioned and stained teeth. Significant differences in several characters are found between porpoise tooth samples from the Canadian east coast and West Greenland, between Iceland, the North Sea, and Celtic Shelf, as well as sub-divisions within the North Sea, and between the North Sea, Skagerrak, Kattegat, Inner Danish waters and the Baltic Sea. The method appears promising if used on groups of known geographic origin. However, it is not certain that any one tooth could be assigned to a particular geographic group, when selected randomly.